Analysis of molybdenite bioleaching by Thiobacillus ferrooxidans in the absence of iron (II) - Pistaccio, Luis (1994)
Thiobacillus ferrooxidans attachment on MoS2 and Mo dissolution are increased by the addition of the tensioactive agent Tween 80 in absence of iron(II), which suggests that the poor bioleaching of MoS2 is caused by its hydrophobic character. Additionally, inhibition ofThiobacillus ferrooxidans growth by the presence of MoO42− and the effect of variable amounts of Tween 80 on bacteria growth and on MoS2 bioleaching are considered in this paper. Data confirm the need of bacterial attachment to insoluble substrate for bioleaching by the direct mechanism.